Asian Symposium on Medicinal Plants, Spices and Other Natural Products - Thanuja, S.; Vasantharuba, S.; Sivakanthan, S. (Asian Symposium on Medicinal Plants, Spices and Other Natural Products, 2018)
Vegetables are rich in antioxidants, which protect against degenerative diseases. This study aimed to compare the antioxidant properties of tomato (Lycopersicon esculentum), carrot (Daucus carota) and bitter gourd (Mormodica charantia). Antioxidants were extracted using ethanol (70 %, v/v). Fresh vegetables were cut in to small pieces, solvent was added (sample: solvent; 1:5 w/v) and shaken for 2 h at 200 rpm at ambient temperature. Then solvent was evaporated to get dry extract, which is used to evaluate total flavonoid content (TFC) [as catechin equivalent (CE)], total phenolic content (TPC) [as gallic acid equivalent (GAE)], antioxidant capacity (AC) [as ascorbic acid equivalent (AAE)] and antioxidant activity [2, 2-Diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity expressed as IC50value, which is inversely proportional to antioxidant activity] on dry matter (DM) basis. Statistical analysis was performed using one way analysis of variance using SAS (9.1). TPC and TFC were highest in bitter gourd (27.47±1.52 GAE/g and 19.36±2.01 mg CE/g, respectively) while carrot showed lowest TPC and TFC (15.25±0.90 GAE/g and 2.67±0.04 mg CE/g, respectively). There were no significance differences among AC of the three vegetables. Tomato and bitter gourd exhibited equal DPPH radical scavenging activity (0.20±0.003 and 0.21±0.008 mg/ml, respectively). Carrot exhibited lowest DPPH radical scavenging activity (0.43±0.017 mg/ml). In conclusion, among three vegetables studied, bitter gourd had highest TPC, TFC and DPPH radical scavenging activity, while, carrot had lowest TPC, TFC and DPPH radical scavenging activity. Furthermore, there was a strong significant positive correlation between TPC and TFC (r = 0.89), TPC and AC (r = 0.61), and TFC and AC (r = 0.90) of selected vegetables. Even though all three vegetables exhibited good antioxidant properties, bitter gourd found to be the better source of antioxidant than others.
Keywords: bitter gourd; total flavonoid content; total phenolic content